Economic crisis, economic methodology and the scientific ideal of physics - Drakopoulos, SA (The Journal of Philosophical Economics, 2016)
The methodological foundations of mainstream economics have been cited as one of the main reasons for its failure to account for the economic crisis of 2008. In spite of this, the status of economic methodology has not been elevated. It is argued that this is due to the persistent aversion towards methodological discourse by most mainstream economists. This attitude has a long presence as exemplified in Frank Hahn’s (1992) work. After focusing on the debate originating after the publication of Hahn’s arguments, the paper offers a categorization of the main explanations for mainstream methodological aversion. Subsequently, it suggests an explanation based on the role of the physics scientific ideal, arguing that the endeavour to achieve the high scientific status of physics by following the methods of physics, contributed to the negative mainstream attitude towards economic methodology. The relevant writings of the extremely influential mainstream economists Irwin Fisher and Milton Friedman, reinforce the assertion that the alleged hard science status of economics renders methodological discussions and especially methodological criticism, rather pointless. The paper also calls for a more systematic discussion of this issue, especially in the wake of the line of argument that links the recent failings of mainstream to its methodological basis